Observation of chemically protected polydimethylsiloxane: towards crack-free PDMS. Issue 37 (18th September 2017) - Adly, N. Y.; Hassani, H.; Tran, A. Q.; Balski, M.; Yakushenko, A.; Offenhäusser, A.; Mayer, D.; Wolfrum, B.
Abstract : We demonstrate a method for crack-free PDMS based on chemical protection using MPTMS. Abstract : The current modification of polydimethylsiloxane (PDMS) substrates via oxygen plasma treatment causes surface cracks. Here, we demonstrate a method to prevent crack formation by chemical treatment. Chemical modification renders the surface hydrophilic for several days and is effective in preserving the elasticity of the PDMS surface at the nanoscale level.